Hematological and Hematopoietic Effects of Bactericidal Doses of Trans-Cinnamaldehyde and Thyme Oil on Cyprinus carpio Juveniles - Kondera, Elżbieta; Bojarski, Bartosz; Ługowska, Katarzyna; Kot, Barbara; Witeska, Małgorzata (Frontiers in Physiology, 2021)
The effects of doses of trans-cinnamaldehyde and thyme oil proved to be bactericidal against Aeromonas spp. on peripheral blood parameters and cellular composition of hematopoietic tissue of Cyprinus carpio were studied. The fish were fed for 2 weeks on diets supplemented with 10 µL/kg of trans-cinnamaldehyde (TC) or 20 µL/kg of thyme oil (TO). Groups TC1 and TO1 were fed diets containing phytochemicals daily, while groups TC2 and TO2 – every two days. Control group and groups TC2 and TO2 on the remaining days were fed plain feed. Blood and head kidney hematopoietic tissue were sampled from all fish at the end of the experiment. In all groups hematological values were within the reference ranges for healthy common carp juveniles. However, blood hemoglobin concentration (Hb) and mean corpuscular hemoglobin concentration (MCHC) were significantly lower in all groups exposed to TC and TO, while mean corpuscular hemoglobin (MCH) in TC1, TO1 and TO2 compared to the control, TC and TO did not affect leukocyte count (WBC), differential leukocyte count, oxidative activity of phagocytes (NBT) or thrombocyte count (Thro). No significant alterations were observed in hematopoietic tissue. The results showed that TC and TO exhibit no considerable hematotoxic effects and trials of their use in treatment of fish infected with Aeromonas spp. may be carried out.